ҚАРАҚАЛПАҚ ДӘСКЕРЛЕРИ – ХАЛҚЫМЫЗДЫҢ МИЛЛИЙ ҚАДРИЯТЫ - Даўлетмуратова, М.Б. (ILIM hám JÁMIYET, 2025)
This article examines the study of the tailoring profession, considered one of the national values of the Karakalpak people, in the system of higher education in the field of art and culture.